Effects of induced damages on the flexural fatigue behavior of glass fiber reinforced epoxy (GREs) - Wong, Teck Kai. (Universiti Malaysia Sarawak, UNIMAS, 2003)
There is a considerable interest in the application of Glass Fiber Reinforced Epoxy (GREs) and its structure in aircraft, as well as in sports and leisure goods. When attempting to design a composite structure, it is beneficial to be able to predict the damage initiation and propagation in order to utilize the material effectively. In this project, the investigations of three-point flexural fatigue behaviour of single and multiple bolted joint connections in single lap made from GREs flat sheets have been carried out.